Pengakuan Hak Ulayat Laut Menurut Hukum Agraria - Lakburlawal, Mahrita Aprilya; Matuankotta, Jenny Kristiana (BAMETI Customary Law Review, 2023)
This article describes the ulayat of customary law communities, especially sea communal rights, and their recognition in agrarian law. The purpose of this writing is to analyze how the existence confession of Community Sea for the local community is recognized in Agrarian Law, guided by normative legal research methods to examine the ambiguity of norms in the UUPA relating to maritime customary rights, using the approaches: statute approach, conceptual approach, as well as an analytical approach. The legal material search technique uses document study techniques, as well as study analysis using qualitative analysis, so it is found that sea communal rights, the same as the position of the ulayat, have not been explicitly regulated in Indonesian Agrarian Law, even though when discussing customary areas as an element of the ulayat, customary areas do not only cover the land (land) but also waters (rivers, lakes, beaches, including the sea), it is clear that if the customary rights of customary law communities are recognized and protected, then so will the sea communal rights.